2014
DOI: 10.2166/wh.2014.079
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review and meta-analysis of the effects of extreme weather events and other weather-related variables on Cryptosporidium and Giardia in fresh surface waters

Abstract: Global climate change is expected to impact drinking water quality through multiple weather-related phenomena. We conducted a systematic review and meta-analysis of the relationship between various weather-related variables and the occurrence and concentration of Cryptosporidium and Giardia in fresh surface waters. We implemented a comprehensive search in four databases, screened 1,228 unique citations for relevance, extracted data from 107 relevant articles, and conducted random-effects meta-analysis on 16 ke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 47 publications
1
32
0
Order By: Relevance
“…A systematic review was developed about the methodologies to quantify the impacts of climate change on undernutrition [33]. A combination of quantitative review and meta-analysis has been carried out about the effects of EWE on Cryptosporidium and Giardia in fresh surface waters [34].…”
Section: Methodsmentioning
confidence: 99%
“…A systematic review was developed about the methodologies to quantify the impacts of climate change on undernutrition [33]. A combination of quantitative review and meta-analysis has been carried out about the effects of EWE on Cryptosporidium and Giardia in fresh surface waters [34].…”
Section: Methodsmentioning
confidence: 99%
“…The oocysts are common in natural waters and can be present in source waters. A SR and MA of the impacts of weather on surface waters indicated that contamination with Cryptosporidium and Giardia was 2.61 and 2.87 higher during and after heavy rainfall [139]. A SR was used to examine the risks of endemic cryptosporidiosis, and found increased risk associated with the unsafe use of water [140].…”
Section: Protozoamentioning
confidence: 99%
“…Hydrodynamic modelling has been shown to represent a valid and cost‐effective support, for decision‐making and understanding of events . Quantitative microbial risk assessment (QMRA) is another widely used tool to estimate health impacts from exposure to Cryptosporidium and other pathogens and has been applied to climate change . The tool, called CC‐QMRA (Climate Change Quantitative Microbial Risk Assessment), quantifies the anticipated impacts in terms of relative infection risks under climate change scenarios for Cryptosporidium and other pathogens and can be used to evaluate impacts of climate change on infection risks from waterborne and foodborne transmissions of Cryptosporidium .…”
Section: Risk Managementmentioning
confidence: 99%
“…153 Indeed, the average odds of identifying Cryptosporidium oocysts in fresh surface waters is 2.61 (95% CI=1.63-4.21; I²=16%) times higher during and after extreme weather events. 154 Shifts in precipitation patterns (intensity and location) is one of the climate change predictions for the future, 155 and this will clearly impact both waterborne and foodborne transmissions of Cryptosporidium, and therefore, future human exposures may differ significantly from current patterns as the climate changes. 156 Hydrodynamic modelling has been shown to represent a valid and cost-effective support, for decision-making and understanding of events.…”
Section: Risk Managementmentioning
confidence: 99%
See 1 more Smart Citation